Ácido e baixas temperaturas sobre Salmonella Enteritidis inoculada em carne suína e sua sobrevivência subsequente ao fluido gástrico simulado - Silva, Simone Quintão [UNESP] (2016)
The objective of this study was to evaluate the acid resistance of Salmonella enterica serovar Enteritidis (S. Enteritidis) in stored pork and in simulated gastric fluid (SGF). A culture of S. Enteritidis was subjected to acid treatment prior to inoculation into pork, stored under refrigeration at frozen temperatures and exposed to SGF. The S. Enteritidis CCS3 and ATCC 13076 strains previously subjected to acid treatment (at pH 4.0-5.0) were inoculated in pork and stored at 4°C and -18°C. Storage at 4ºC did not affect the populations of both S. Enteritidis strains. After 84 days at -18°C, the mean population of both CCS3 and ATCC strains were reduced by 0.8 and 1.5 log cycles, respectively. Prior acid treatment did not enhance the survival of both strains at low temperatures. After acid treatment and low temperature storage, S. Enteritidis ATCC 13076 lost culturability after being exposed to SGF for 10 minutes. In contrast, S. Enteritidis CCS3 was tolerant until three hours of SGF exposure. S. Enteritidis CCS3 submitted to pH 4.0 was more tolerant to SGF exposure than when submitted to pH 4.5, 5.0 and without acid treatment. Therefore, this study indicates that exposure to an acidic and cold environment during processing enhanced the ability of S. Enteritidis to survive in the gastric environment of the human stomach, possibly increasing the risk of a Salmonella infection after consumption of pork.